The mid-Oxfordian (Late Jurassic) positive carbon-isotope excursion recognised from fossil wood in the British Isles - Pearce, C; Hesselbo, S; Coe, A (2005)
The carbon-isotope ratios of fossil wood have recently been confirmed as a proxy for changes in the isotopic composition of palaeoatmospheres. Carbon-isotope data from fossil wood samples collected from the Jurassic (Oxfordian) Staffin Shale Formation on the Isle-of-Skye, Scotland (Boreal/Sub-Boreal ammonite zonation) reveal a long-term positive carbon-isotope excursion of at least 3‰. This excursion reaches a maximum in the mid-Oxfordian, and closely matches the carbon-isotope ratios previously reported from belemnites collected from the same section and carbon-isotope data from carbonates in other European sections. This confirms that the mid-Oxfordian positive carbon-isotope excursion affected the total exchangeable carbon reservoir. Fossilised wood samples collected at a higher stratigraphic resolution, but over a shorter interval from the Corallian Group in Dorset, England (antecedens, parandieri and cautisnigrae subzones; NW European ammonite zonation) show considerable scatter in their carbon-isotope ratios, and no trends are discernable. The combined Isle-of-Skye and Dorset dataset shows that the long-term Oxfordian positive carbon-isotope trend coincides with a long-term relative sea-level change, and that the most positive carbon-isotope ratios occur across the plicatilis-transversarium biozonal boundary (Sub-Mediterranean ammonite zonation). This implies that the carbon-isotope excursion was not caused by the well-documented rise in sea-level in the transversarium Zone. Although very low carbon-isotope ratios from fossil wood samples are recorded from the Nodular Rubble Member (parandieri Subzone) of Dorset, there is not a sufficiently coherent signal to ascribe these values to the gas-hydrate dissociation event previously hypothesized from the carbon-isotope ratios of Tethyan marine carbonates. A microscopal analysis of the charcoalified debris from the Staffin Shale Formation indicates a prevalence of the wood genus Cupressinoxylon, derived from a cheirolepidiaceaen conifer. © 2005 Elsevier B.V. All rights reserved.